STRATEGI MANAJEMEN SARANA PRASARANA DALAM PENINGKATAN EFEKTIVITAS DAN KONDUSIVITAS PEMBELAJARAN DI SMK UNGGULAN NU MOJOAGUNG - Alfiana Herdiati; Asep Kurniawan (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the infrastructure management strategy in improving the effectiveness and conduciveness of learning at SMK Unggulan NU Mojoagung. Using a qualitative approach with a descriptive case study research type, data collection was conducted through observation, interviews, and documentation. The research subjects involved the principal, vice principal for infrastructure, class teachers, and students. The results of the study indicate that infrastructure management is implemented through systematic stages that include needs-based planning, procurement, use, ongoing maintenance, and monitoring and evaluation. Optimization of physical facilities and practice rooms has been proven to facilitate teachers in delivering materials and significantly accelerate student understanding, thereby increasing learning effectiveness. In addition, the management of a clean, safe, and organized learning environment has successfully created a conduciveness that supports student focus, motivation, and discipline. In conclusion, despite still facing budget constraints, a systematic and participatory infrastructure management strategy has proven significant in realizing an effective, productive, and optimal learning process